2001
DOI: 10.1128/aem.67.7.3309-3313.2001
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Cryptosporidium parvum Oocyst Infectivity In Vitro by Using the Membrane Filter Dissolution Method for Recovering Oocysts from Water Samples

Abstract: Exposure of Cryptosporidium parvum oocysts to solutions used for cellulose acetate membrane (CAM) dissolution filtration reduced their infectivity in HCT-8 cells. Ethanol (95% [vol/vol] and 70% [vol/vol]) aloneand short exposure times to acetone decreased infectivity. These findings contrast with similar experiments using excystation assays and infectivity in mice.Successful detection of Cryptosporidium parvum oocysts in water samples depends on efficient filtration methods to recover oocysts. Method 1623 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…24 Processing of C. parvum oocysts by the CAM-filter dissolution method does not alter their infectivity as tested in vivo by mouse bioassay, 25 although in vitro testing indicates that oocyst infectivity decreases. 26 Surface elution ensures recovery of particles derived from the exoskeleton of the fly, and homogenization releases the particles within the digestive tract. 15 The resulting pellets were stored in 200 L of 95% ethanol at 4°C 18 until analyzed by FISH and FITCconjugated MAb.…”
Section: Methodsmentioning
confidence: 99%
“…24 Processing of C. parvum oocysts by the CAM-filter dissolution method does not alter their infectivity as tested in vivo by mouse bioassay, 25 although in vitro testing indicates that oocyst infectivity decreases. 26 Surface elution ensures recovery of particles derived from the exoskeleton of the fly, and homogenization releases the particles within the digestive tract. 15 The resulting pellets were stored in 200 L of 95% ethanol at 4°C 18 until analyzed by FISH and FITCconjugated MAb.…”
Section: Methodsmentioning
confidence: 99%
“…CAM dissolution in 100% acetone is an alternative to the elution procedure [71]. However, it seems not to be appropriate for virulence studies because viability of protozoa is reduced after dissolution [72].…”
Section: Concentration Techniquesmentioning
confidence: 99%
“…Previous studies have shown that vital dye staining and excystation rates may overestimate the number of infectious oocysts present (2,4,8,9). Infectivity assays using animals are expensive, and it is difficult to obtain quantitative results.…”
mentioning
confidence: 99%
“…Infectivity assays using animals are expensive, and it is difficult to obtain quantitative results. However, in vitro infectivity assays are useful for quantitatively measuring antimicrobial effects of disinfectants against C. parvum oocysts (4,9).…”
mentioning
confidence: 99%